PENGARUH EKSTRAK BEBERAPA JENIS TANAMAN SEBAGAI INSEKTISIDA NABATI UNTUK MENGENDALIKAN SERANGAN LALAT BUAH Bactrocera sp. (Diptera:Tephritidae) PADA TANAMAN CABAI RAWIT - Gafur Gafur; Alam Anshary (AGROTEKBIS : JURNAL ILMU PERTANIAN (e-journal), 2022)
This study aims to determine the effect of extracts of several types of plants as plant-based insecticides to control fruit fly attacks on cayenne pepper plants. This research was conducted from February to April 2017 in Lumbutarombo Village, Banawa Selatan District, Donggala Regency, Central Sulawesi. This study used a randomized block design (RBD), consisting of 5 treatments namely: A0 = Control, A1 = Patchouli Extract, A2 = Basil Extract, A3 = Lemongrass Extract, and A5 = Lime Extract. From the results of the study showed that lemon grass leaf extract was more effective in controlling the intensity of the fruit fly attack on the chili plants. Based on the results of observation, the highest average intensity of fruit fly attack in A0 (control) treatment was 6.83%, while the lowest intensity of attack was in A3 treatment (lemongrass leaf extract), which was 2.16%. Based on observations it can be concluded that the treatment of lemongrass leaf extract as a vegetable insecticide significantly affects the intensity and is more effective in controlling the attack of Bactrocera sp. in chili plants.